2004
DOI: 10.1182/blood-2003-05-1679
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of P-selectin glycoprotein ligand-1 induces death of activated T cells

Abstract: Increasing evidence has shown that death signaling in T cells is regulated in a complicated way. Molecules other than death receptors can also trigger T-cell death. Here, we demonstrate for the first time that P-selectin glycoprotein ligand-1 (PSGL-1) or CD162 molecules crosslinked by an anti-PSGL-1 monoclonal antibody, TAB4, can trigger a death signal in activated T cells. In contrast to classic cell death, PSGL-1-mediated T-cell death is caspase independent. It involves translocation of apoptosis-inducing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…Contrasting their data, we failed to observe any significant adverse effect of TAB4 on the repopulation of lymphocytes in our animal studies. Our in vitro and in vivo results indicated that TAB4 must target T cells at a particular stage of activation, yet such a preferential susceptibility is not correlated with expression levels of PSGL-1 from the previous data [6]. It was reported that P-selectin binds to an exclusive form of PSGL-1 on Th1 cells, but not on Th2 cells [35].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Contrasting their data, we failed to observe any significant adverse effect of TAB4 on the repopulation of lymphocytes in our animal studies. Our in vitro and in vivo results indicated that TAB4 must target T cells at a particular stage of activation, yet such a preferential susceptibility is not correlated with expression levels of PSGL-1 from the previous data [6]. It was reported that P-selectin binds to an exclusive form of PSGL-1 on Th1 cells, but not on Th2 cells [35].…”
Section: Discussionmentioning
confidence: 64%
“…The physiological importance of PSGL-1 was believed to be confined to mediating leukocyte recruitment, until we reported recently a novel function of PSGL-1 which can be cross-linked by antibody and can lead to death of activated T cells [6]. Levesque et al [34] previously demonstrated the role of PSGL-1 in mediating hematopoiesis by inducing apoptosis of a subpopulation of CD34 + CD38 -progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations